A TPACK-in Practice Model for Enhancing EFL Students’ Readiness to Teach with Ed-Tech Apps - Lisa, Agatha; Faridi, Abdurrachman; Bharati, Dwi Anggani Linggar; Saleh, Mursid (International Journal of Interactive Mobile Technologies (iJIM), 2021)
In Indonesia, educational technology courses have been offered in teacher preparation programs to equip students with theoretical knowledge and practical skill of utilizing technology in skill-based language teaching. Despite this, empirical studies focused on online training for EFL teacher candidates on using digital tools appropriately for pedagogical purposes and adjusting to traditional learning processes remain unexplored. Therefore, to address this gap, the present study attempts to investigate the design and implementation of a TPACK-in practice model to enhance students’ preparedness to face the rapidly-growing digital world and, more importantly, understand post-pandemic pedagogy. For this purpose, a qualitative case study was adopted. The data were obtained from multiple sources, including field notes, video-recorded classroom observation, one-on-one online interviews, and task documentation. The population of this research included 163 students in the 5th semester of the English Language Education Study Program of a university in Yogyakarta, Indonesia. We selected one class randomly, consisting of 40 pre-service English teachers during the odd semester of the 2020/2021 Academic Year. Findings demonstrate: 1) lesson activity-specific model in the educational technology course, 2) students’ reports on their hands-on learning experiences in designing teaching-learning activities with a variety of digital tools, 3) the perceived benefits of reviewing ed-tech apps, and 4) challenges encountered by students in completing their project. Finally, pedagogical implications are presented with proposed suggestions offered for future research directions in replicating the study.